Knowledge mapping and emerging trends in pediatric hemiplegia research: a bibliometric study spanning 1982–2025 - Li, Xiaoli; Guo, Ya; Niu, Lingchuan (Frontiers in Neurology, 2025)
BackgroundPediatric hemiplegia is a significant neurological condition that impacts motor function and quality of life. This bibliometric analysis aimed to evaluate research trends, collaboration patterns, and emerging topics in pediatric hemiplegia research.MethodsPublications were retrieved from the Web of Science Core Collection database spanning from 1982 to 2025. The analysis was conducted using VOSviewer, CiteSpace, and R-bibliometrix to examine contributions of countries, institutions, authors, journals, and keywords.ResultsA total of 1,840 publications were analyzed, showing consistent growth with an annual growth rate of 8.69%. The United States emerged as the leading contributor with 393 publications, followed by Italy (137) and the United Kingdom (124), with strong international collaboration networks evident among 64 countries. The University of London demonstrated the highest institutional productivity with 142 publications, while Royal Children’s Hospital showed the strongest collaborative connections. Developmental Medicine and Child Neurology ranked as the most productive journal with 195 publications and highest citation impact. Boyd RN and Gordon AM were identified as the most influential authors based on h-index metrics and collaboration strength. Keyword analysis revealed five distinct research clusters, with “alternating hemiplegia,” “mutations,” “classification,” and “risk factors” emerging as current research hotspots since 2017.ConclusionThis bibliometric analysis provides a comprehensive overview of research progress and identifies key hotspots in pediatric hemiplegia research, revealing the field’s evolution from basic clinical descriptions to advanced genetic and classification studies. These findings offer valuable insights for researchers and clinicians to understand current research priorities and guide future investigations in pediatric hemiplegia management and treatment strategies.